Manufacturing yogurt and fermented milks - Chandan, Ramesh C.; Kilara, Arun (Wiley-Blackwell, 2013)
Melding the hands-on experience of producing yogurt and fermented milks over four decades with the latest in scientific research in the dairy industry, editor Chandan and his associate editors have assembled experts worldwide to write Manufacturing Yogurt and Fermented Milks, 2nd Edition